2017
DOI: 10.1016/j.sjpain.2016.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of expectation on pain assessment of lower- and higher-intensity stimuli

Abstract: AbstractBackground and aimsPain modulation via expectation is a well-documented phenomenon. So far it has been shown that expectations about effectiveness of a certain treatment enhance the effectiveness of different analgesics and of drug-free pain treatments. Also, studies demonstrate that people assess same-intensity stimuli differently, depending on the experimentally induced e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
0
5
0
2
Order By: Relevance
“…Specifically, in prior experimental pain literature, intensity ratings have been associated with the sensorydiscriminative aspect of pain while unpleasantness ratings are used to assess pain's affective-motivational component (Auvray et al, 2010). As anxiety and expectations are both known to influence evaluations of experimentally induced pain (Ružić et al, 2017;Tang & Gibson, 2005), participants also provided anxiety and pain anticipation ratings, though these ratings are not considered in the present analyses. Open-ended verbal descriptions of the pain experience were collected to assess the presence of language-congruent differences in pain coping (Schulz et al, 2013).…”
Section: Session Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, in prior experimental pain literature, intensity ratings have been associated with the sensorydiscriminative aspect of pain while unpleasantness ratings are used to assess pain's affective-motivational component (Auvray et al, 2010). As anxiety and expectations are both known to influence evaluations of experimentally induced pain (Ružić et al, 2017;Tang & Gibson, 2005), participants also provided anxiety and pain anticipation ratings, though these ratings are not considered in the present analyses. Open-ended verbal descriptions of the pain experience were collected to assess the presence of language-congruent differences in pain coping (Schulz et al, 2013).…”
Section: Session Overviewmentioning
confidence: 99%
“…As a key feature of Hispanic culture (Taylor et al, 2012), language usage may meaningfully contribute to pain experiences. Further study could examine how other cultural patterns, e.g., familismo (i.e., placing familial needs ahead of individual needs) or machismo (i.e., masculine aggression and strength) commonly expressed in Hispanic cultures (Ingoldsby, 1991) may influence factors, such as verbal suggestibility or coping strategies, which are known to alter pain responses (Jensen et al, 1991;Ružić et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Pain perception is strongly influenced by cognitive factors such as the expected severity or intensity of impending pain, or expected changes in pain ( Villemure and Bushnell, 2002 , Rhudy et al, 2006 , Gollub et al, 2018 , Henderson et al, 2020 ). Expectation effects can also have a strong influence on experimentally-induced pain for research purposes, and on the effectiveness of pain treatments, such as when coupled with an inactive treatment to produce placebo or nocebo effects ( Ružić et al, 2017 , Evers et al, 2018 ). Behavioral studies have demonstrated that expectation of higher pain results in increased pain ratings, and expectation of lower pain results in lower pain ratings ( De Pascalis et al, 2002 , Ružić et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…94 Zdravstveni djelatnici mogu modulirati kako specifična očekivanja o efikasnosti lijeka tako šire psihološko sta-kako je samo manipulacija očekivanjima bez ikakvog tretmana učinkovita, primjerice, u smanjenju boli. [95][96][97][98] Posebno je pak zanimljiva i ilustrativna činjenica proizašla iz paradigme prikrivenog davanja lijekova za ublažavanje boli. [99][100][101]73 .…”
Section: Slikaunclassified